Sistem Informasi Manajemen Klinik Basmallah Jambi Berbasis Web - Pratama, Bimo; Sharipuddin, Sharipuddin (LPPM Universitas Dinamika Bangsa, 2023)
The clinical management system at the Jambi Basmallah Clinic is still done manually so it has problems such as errors in recording general patient data or insurance patients, searching for available drug data because there is no data for drug stock, damage and data loss due to existing storage media only. in the form of archived documents, difficulties in making reports so that it takes more time to implement. Based on the existing problems, a clinical management information system is needed that can assist in minimizing the existing problems. This study uses modeling tools in the form of Usecase diagrams, Activity diagrams, and class diagrams. The purpose of this study is to design a prototype system that can provide an overview of management information systems to the clinic. The results of this study are a prototype design of a clinical management information system that can be implemented later as a solution to the problems that exist at the Jambi Basmallah Clinic.